A defensoria pública e o acordo de não persecução penal: estudo de caso na comarca de Manaus – Amazonas - Dias, Eduardo Augusto da Silva (2024)
This research primarily conducts a case study on non-criminal prosecution agreements in the Manaus jurisdiction, with the goal of examining whether these procedures prejudice the right of defense for those assisted by the Public Defender’s Office. The hypothesis posits that consensual procedures in criminal cases are influenced by power and knowledge relations, making the decision to accept or reject a proposed agreement a strategic evaluation aimed at harm reduction. The theoretical framework relies on the studies of Michel Foucault and Jürgen Habermas: Foucault for identifying a microphysics of power and knowledge, and Habermas for his theory of communicative action, which advocates for mutual understanding and consensus but requires a coercion-free relationship, something lacking in consensual criminal justice. This reinforces an instrumental and strategic logic, verifiable through Foucault’s archaeological and genealogical methods. This study is divided into five chapters, organized as follows: the first chapter provides a philosophical reference on defensive ethics and the notion of justice, focusing on the construction of subjectivity in Stoicism, which underpinned Christianity and is echoed in the judicial practices of democratic, ostensibly secular States, exemplified by the confession. The second chapter addresses the main aspects of the Theory of Communicative Action, which underpins mutual understanding, and interacts with Foucault’s notions of power/knowledge. It concludes that the lifeworld, as defined by Habermas, depends on the discursive reference of each interlocutor. In unequal societies like Brazil, where violence against certain groups persists, this is evident in the selective characteristics of penal knowledge, and achieving mutual understanding involve more than recognizing a validity claim but entails the imposition of wills through subtle coercion, as seen in non-criminal prosecution agreements. The third chapter analyses the mechanisms of knowledge and power reproduction in practical contexts. The fourth chapter presents an empirical study divided into three investigative sections: a brief overview of the impact of non-criminal prosecution agreements on certain penal laws, a survey of public defenders working in Criminal Law in Manaus, and a case study on non-criminal prosecution agreement hearings held in 2022 and 2023. The fifth chapter, considering the rise of consensual criminal justice where cases may be summarily resolved through agreements without discussing the merits of guilt, proposes strengthening technical defense mechanisms in the pre-trial phase. This phase includes mandatory presence of public defenders during police investigations and establishing a role for a public defender of guarantees to participate obligatorily in preliminary phases, including confidential acts currently exclusively managed by prosecuting authorities, the Judicial Police, and the Public Prosecutor’s Office. Keywords: Public Defender's Office; Non-criminal Prosecution Agreement; Consensual Criminal Justice; Defensive Ethics; Custos vulnerabilis.